FOXM1 network in association with TREM1 suppression regulates NET formation in diabetic foot ulcers. (20th July 2022) - Sawaya, Andrew P; Stone, Rivka C; Mehdizadeh, Spencer; Pastar, Irena; Worrell, Stephen; Balukoff, Nathan C; Kaplan, Mariana J; Tomic‐Canic, Marjana; Morasso, Maria I
Abstract: Diabetic foot ulcers (DFU) are a serious complication of diabetes mellitus and associated with reduced quality of life and high mortality rate. DFUs are characterized by a deregulated immune response with decreased neutrophils due to loss of the transcription factor, FOXM1. Diabetes primes neutrophils to form neutrophil extracellular traps (NETs), contributing to tissue damage and impaired healing. However, the role of FOXM1 in priming diabetic neutrophils to undergo NET formation remains unknown. Here, we found that FOXM1 regulates reactive oxygen species (ROS) levels in neutrophils and inhibition of FOXM1 results in increased ROS leading to NET formation. Next generation sequencing revealed that TREM1 promoted the recruitment of FOXM1 + neutrophils and reversed effects of diabetes and promoted wound healing in vivo . Moreover, we found that TREM1 expression correlated with clinical healing outcomes of DFUs, indicating TREM1 may serve as a useful biomarker or a potential therapeutic target. Our findings highlight the clinical relevance of TREM1, and indicates FOXM1 pathway as a novel regulator of NET formation during diabetic wound healing, revealing new therapeutic strategies to promote healing in DFUs. Synopsis: The FOXM1 transcription factor modulates NETs by regulating ROS during diabetic wound healing. TREM1 contributes to the clinical healing outcome and promotes FOXM1 + neutrophil recruitment to enhance diabetic wound healing. Diabetic foot ulcers (DFUs) are characterized by a suppressed inflammatory response with increased NET formation. Inhibition of FOXM1 in human neutrophils increases ROS levels leading to NET formation. Topical TREM1 application promotes recruitment of FOXM1 + neutrophils and enhances diabetic wound healing in mice. TREM1 expression and NET formation contributes to the clinical healing outcome of DFUs and may serve as potential biomarker. Abstract : The FOXM1 transcription factor modulates NETs by regulating ROS during diabetic wound healing. TREM1 contributes to the clinical healing outcome and promotes FOXM1 + neutrophil recruitment to enhance diabetic wound healing.